Ligation of Left Atrial Appendage during Off-Pump Coronary Surgery - Enginoev, Soslan; Koz'min, Dmitry; Magomedov, Gasan; Makeev, Sergey; Chernov, Igor; Ilov, Nikolay; Tarasov, Dmiry; Zhigalov, Konstantin; Weymann, Alexander (The Thoracic and Cardiovascular Surgeon, 2019)
Objective The main purpose of this article is to evaluate an impact of epicardial ligation of the left atrial appendage (LAA) in patients with atrial fibrillation (AF) undergoing off-pump coronary artery bypass grafting (OPCAB) on the development of ischemic stroke and mortality.Methods From 2009 to 2013, a total of 125 patients (86.4% men, mean age 64 ± 7 years, 95% confidence interval: 61–65 years) received a combined OPCAB and LAA ligation because of coronary artery disease and AF. All the subjects were divided into two groups: group 1 (n = 57)—LAA ligation during OPCAB, group 2 (n = 68) without LAA ligation during OPCAB. Primary endpoints were postoperative incidence of ischemic stroke and mortality.Results No difference in the number of ischemic stroke (0 vs. 5.9%) and death (0 vs. 4.4%) in both groups during the hospital period (p > 0.05). Median overall follow-up was 41 (22–61) months: without difference for groups (p > 0.05). During follow-up, there was a difference in the number of ischemic stroke (0 vs. 17.6%, p < 0.001), while there was no difference in mortality in two study groups (5.3 vs. 16.2%, p > 0.05).Conclusion Epicardial ligation of LAA during OPCAB in patients with AF may reduce the risk of ischemic stroke in long-term follow-up and does not affect the mortality.
Keywords: off-pump coronary surgery; left atrial appendage; atrial fibrillation